Dissolution Method Validation with Reverse Phase Chromatographic Method for Determination of Eltrombopag Drug Release in Dissolution Samples of Tablets: Dissolution Method Validation with Reverse Phase Chromatographic Method for Determination of Eltrombopag Drug Release in Dissolution Samples of Tablets - Patel, Dharti (International Journal of Pharmaceutical & Biological Archive, 2020)
The present analytical work is a unique method development and validation for the determination of dissolution of Eltrombopag using reverse phase high-performance liquid chromatography (HPLC) with isocratic elution technique. HPLC method for quantification of drug in dissolution samples of Eltrombopag tablet is developed and validated. About 0.5% polysorbate 80 in phosphate buffer of pH −6.8 is used as dissolution medium and paddle (USP-II) as apparatus at 50 rpm. The sample was withdrawn after 45 min. The developed HPLC method was used for quantitative estimation of drug release in dissolution samples of Eltrombopag tablet. Here, the stationary phase used was Xbridge C18 (50 mm × 4.6 mm × 5 μm), mobile phase was 25% ammonium formate and 75% acetonitrile. pH of the buffer solution was maintained at 3.0, flow rate 1.0 ml/min. Eluted material underwent for monitoring at the detector wavelength of 230 nm. Retention time for Eltrombopag was found to be 2.16 min; and linearity range was 3.516 µg/mL–131.862 µg/mL. The new method was evaluated according to the ICH guideline and as far as validation results are concern correlation coefficient value that was 1.0000 for the compound, percentage recovery 99.4%, and repeatability results relative standard deviation 0.6 for Eltrombopag. The developed HPLC method was found to be a simple and rapid one for regular analysis in professional laboratory.